Implementation of Electronic Traffic Law Enforcement in the Settlement of Traffic Violation Cases in the Jurisdiction of Directorate of Traffic Police Bengkulu Regional Perspective Of Fiqih Siyasah - Nopan Wiranata; Ismail Jalili (CV. Doki Course and Training, 2023)
This research aims to analyze the application of Electronic Traffic Law Enforcement in efforts to prosecute traffic violations in the jurisdiction of the Bengkulu Regional Police Traffic Directorate using the perspective of Siyasah Dusturiyah. This research is a qualitative-empirical research using documentation and interview data collection methods. This research found that the use of ETLE in efforts to prevent traffic violations in Bengkulu City is one of the efforts made by the Traffic Directorate (Ditlantas) of the Bengkulu Regional Police to deal with the problem of high traffic violations occurring in the Bengkulu City Traffic Space. This also shows the need for more public awareness to avoid harm and negligence in obeying the regulations set by Ulil Amri. This research found that (1) Bengkulu Police Traffic Directorate's efforts to regulate traffic and reduce violations of traffic regulations are by Law Number 22 of 2009 concerning Road Traffic and Transportation. The Bengkulu Police Traffic Directorate has also carried out outreach and supervision of the implementation of ETLE in Bengkulu City. Apart from that, the implementation of ETLE is also intended as a form of transparency in the payment of traffic violation fines to avoid extortion by unscrupulous ticket officers. (2) Judging from siyasah dusturiyah, the Bengkulu Police's efforts in implementing ETLE as a way to resolve traffic violation cases are seen as an effort to bring benefit to the community and avoid damage (mafsadah) that could potentially occur in the middle of the Traffic Space.